(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
The degradation of Rhodamine B (RB) by cadmium antimony carbon (Cd-Sb/C) catalyst under visible light was examined. The layered double hydroxide was successfully prepared from cadmium fluoride (CdF2), antimony chloride (SbCl3), and rice husks activated carbon, and then characterized by X-ray Diffraction (XRD) Scanning Electron Microscopy (SEM) and Fourier Transform Infrared (FTIR) methods. The peaks at 2Ó¨ 23.4 and 35.5 in the XRD result confirmed the presences of LDH. The effect of contact time, catalyst dosage, pH and initial concentration, on the photo degradation of Rhodamine B were investigated. The experimental results showed that after 100min visible light irradiation, the percentage degradation using 200mg Cd-Sb/C, pH 7 and 3ppm Rhodamine B concentration reached to 76.22%. For kinetics studies the data obtained were analysed using pseudo first order and pseudo second order kinetic models. From the linear regression coefficient values the data were found to be best fitted to pseudo second order kinetics. The results revealed that the Cd-Sb/C show good catalytic activity.